The Dispute over the Ottoman legacy as a part of contemporary identity discussions in Albania - Czekalski, Tadeusz (Balcanica Posnaniensia. Acta et studia, 2018)
The dispute over the Ottoman heritage and its influence on the identity and evolution of the Albanian nation is one of the fundamental tendencies in the identity discussions in post-communist Albania. The European aspirations of the Albanians encouraged the victimization of identity discourse and promoted seeing contemporary Albanian problems in the context of the collapse of Ottoman Empire. Demands to revise history proposed by of the Democratic Party of Albania after 2009 elections fostered the reinforcement of the mythologized vision of history but also lead to the conflict of the memory of Albania and Turkey, whose policies of memory form part of the current political needs of both countries